Network meta-analysis of treatment regimens for inoperable advanced hepatocellular carcinoma with portal vein invasion - Li MF; Leung HW; Chan AL; Wang SY (Dove Medical Press, 2018)
Ming-Feng Li,1,2,* Henry WC Leung,3,* Agnes LF Chan,4 Shyh-Yau Wang2,* 1Department of Medical Imaging, Buddhist Tzu-Chi General Hospital, Hualien, Taiwan; 2Department of Radiology, An-Nan Hospital, China Medical University, Tainan, Taiwan; 3Department of Radiation Oncology, An-Nan Hospital, China Medical University, Tainan, Taiwan; 4Department of Pharmacy, An-Nan Hospital, China Medical University, Tainan, Taiwan *These authors contributed equally to this work Purpose: We assessed the efficacy and safety of different modalities using the network meta-analysis for inoperable hepatocellular carcinoma (HCC) with portal vein invasion. The interested modalities included stereotactic body radiotherapy (SBRT) combined with transarterial chemoembolization (TACE), three-dimensional radiotherapy (3D-RT) combined with hepatic arterial infusion chemotherapy (HAIC) or TACE, TACE plus sorafenib, and use of SBRT, HAIC, sorafenib, and TACE alone. Methods: PubMed and Cochrane Library electronic databases were systematically searched for eligible studies published up to June 2017. We used network meta-analysis to compare the disease control rate (DCR) and severe adverse events for the eight interested regimens included in this analysis. Study quality was assessed following the Grading of Recommendations, Assessment, Development and Evaluations method. Results: Fifteen studies published between 2010 and 2016 involving a total of 2,359 patients were enrolled in this network meta-analysis. With indirect comparison of DCR and overall safety, the pooled results showed that RT plus HAIC was the most effective regimen in treating advanced HCC with portal vein tumor thrombosis, followed by RT plus TACE. HAIC alone and sorafenib combined with HAIC appeared least effective intervention regimens. The incidence of treatment-related adverse events of grade 3 or 4 occurred less in the patients who received SBRT alone compared with other interested regimens. Conclusion: 3D-RT combined with HAIC or TACE showed more favorable treatment responses compared with other regimens in advanced HCC patients with portal vein tumor thrombosis. Keywords: SBRT, HAIC, 3D-RT plus HAIC, sorafenib, network meta-analysis, PVTT